Impact of Corn Flour Substitution on the Hedonic Quality of Mocaf Tartlet Shells - Dearni Br Sipayung; Diwyacitta Antya Putri; Mauren Gita Miranti; Raida Amelia Ifadah (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
The purpose of this study was to examine the impact of corn flour substitution on the sensory characteristics of mocaf-based tartlet skin, while determining the most optimal formulation. Variations of corn flour substitution consisting of four levels (10%, 20%, 30%, and 40%) to mocaf flour were tested using a completely randomized experimental design. The hedonic quality test involved 30 semi-trained panelists who assessed four sensory attributes including color, aroma, taste, and texture using a rating scale of 1 to 4. Data were analyzed using the Kruskal-Wallis non-parametric test followed by a post-hoc test using Dunn-Bonferroni with a correction of α' = 0.05/6 = 0.0083. The results showed that corn flour substitution had a significant effect (p < 0.05) on the color (p < 0.001), aroma (p = 0.006), and texture (p = 0.003) of mocaf-based tartlet skin, but had no significant effect on the taste (p = 0.200). The best formulation was found in sample A4 (60% mocaf: 40% corn flour) which produced a characteristic brownish yellow color, dominant corn aroma, and the crispiest texture.